Kesadaran Wajib Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pada KPP Pratama Padang Satu - Denny Novi Satria; Rahma Annisa (JURNAL PUNDI, 2022)
The purpose of this study is to provide empirical evidence about the effect of Taxpayer Awareness and Tax Sanctions on Taxpayer Compliance at KPP Pratama Padang Satu. This research uses quantitative research methods. The data obtained from primary data is through questionnaires by using incidental sampling technique and by using the slovin formula. The population in this study were all individual taxpayers registered at KPP Pratama Padang Satu in 2020 using 100 samples in this study consisting of individual taxpayers registered at KPP Pratama Padang Satu.The results of the study produce a coefficient of determination which indicates that taxpayer awareness and tax sanctions affect taxpayer compliance by 28.4%, while 71.% is influenced by other variables not examined in this study. Keywords: Taxpayer Awareness, Tax Sanctions, Taxpayer Compliance